INDEKS KEPUASAN MASYARAKAT TERHADAP PELAYANAN KANTOR DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU KABUPATEN BERAU: INDEKS KEPUASAN MASYARAKAT TERHADAP PELAYANAN KANTOR DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU KABUPATEN BERAU - Abdul Hakim (Prodi Ekonomi Pembangunan, Universitas Muhammadiyah Berau, 2019)
The Regulation of the Minister of Administrative Reforms No. 14 in 2017 as a regards of Drafting Guidelines of Public Satisfaction Surveys, Public Service Provider Units certify that the State Civil Service (ASN) should providing services to the community professionally. Professionalism highly determined by a person’s competence and capability in working. Related to the services, it could not be establish optimally without the readiness of the State Civil Apparatus to enforce their tasks and responsibilities in serving the community. Based on the results of this study, the conclusions can be drawn as follow : The measurement results of the Community Satisfaction Index at Investment and One Stop Integrated Services Board of Berau Regency totally was 79.01 with B /